(x+49)(x+4)=O

Simple and best practice solution for (x+49)(x+4)=O equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x+49)(x+4)=O equation:


Simplifying
(x + 49)(x + 4) = O

Reorder the terms:
(49 + x)(x + 4) = O

Reorder the terms:
(49 + x)(4 + x) = O

Multiply (49 + x) * (4 + x)
(49(4 + x) + x(4 + x)) = O
((4 * 49 + x * 49) + x(4 + x)) = O
((196 + 49x) + x(4 + x)) = O
(196 + 49x + (4 * x + x * x)) = O
(196 + 49x + (4x + x2)) = O

Combine like terms: 49x + 4x = 53x
(196 + 53x + x2) = O

Solving
196 + 53x + x2 = O

Solving for variable 'x'.

Reorder the terms:
196 + -1O + 53x + x2 = O + -1O

Combine like terms: O + -1O = 0
196 + -1O + 53x + x2 = 0

The solution to this equation could not be determined.

See similar equations:

| x^2-5x+6.25-14=6.25 | | 1x-2y=10 | | w+9=-7 | | 5-4x=x-1.5 | | 5x-0.8=0.2+3x | | 6y-1y-12= | | =6z-(3z-6)+(7-8z) | | 15=3x-6x-3 | | 6y^2+8y-9y-12= | | X+x+1+x+2=274 | | -36=p-6 | | 3=18x+6x^2 | | G(x)=8sin(5x^6) | | 6y^2+8y-8y-12= | | k^2+12k=-35 | | 2x^3-2x^2+7x-40=0 | | 9d+d-d+2-3d=0 | | 6y^2+8y-12= | | (49x^2)-(25)=0 | | 3(x+y)-2(2y+x)+y= | | 1+n/3=-6 | | 2x+8+2x=10+2x+12 | | 1.2+y=-8 | | 4x-5=6x-13 | | 5-(x+3)+3x+3(x+2)= | | -18+12-3= | | (9x+9)+(-12x+24)= | | 4(x+3)+(x+6)+2(x-3)= | | 160s+465(88-s)=19265 | | n^2+14n-95=0 | | 0=7x-28 | | (x-5i)(x+5i)=0 |

Equations solver categories